Genetics of helminth infections: Immune system response, insights into host-parasite interaction, and drug resistance. - Aldamigh, Mashael Abdullah (Journal of Advanced Veterinary and Animal Research, 2025)
Helminthiases, which are caused by parasitic helminths, have a big effect on global health, especially in places with few resources. They cause a lot of illness and put a lot of strain on society and the economy. Understanding the prevalence, transmission, and impact of helminthiases is crucial for effective control and prevention. Molecular population genetics has been pivotal in understanding helminth dynamics, including species identification, hybridization, and drug resistance. However, deeper insights require broader genetic datasets. Several genomes have been sequenced using genomic technologies, which has changed the way helminth researchers do their work and made it easier to compare genomes and find conserved genetic elements. Genetic factors of the host also affect susceptibility. Genome-wide association studies have found candidate genes that are connected to susceptibility or resistance. Helminth infections trigger Type 2 immune responses involving various immune cells, cytokines, and mediators. Recent discoveries show how non-immune cells like stromal, epithelial, and neural cells control these responses. Genetic differences between the host and the parasite affect how they interact. Helminths use immunomodulatory molecules to hide from immune surveillance. The concept of host disease tolerance, maintaining health despite infection, is gaining attention. The emergence of drug resistance poses a challenge, emphasizing the need to understand the genetic mechanisms underlying anthelmintic resistance. Genomic approaches offer promising avenues for interventions, including vaccine development and RNA interference. Challenges in helminth genetics research include genetic heterogeneity, limited sample sizes, and technical constraints. Using both functional genomics and multi-omics methods together can help us fully understand helminth genetics and plan effective treatments. Genomic studies have helped us learn more and find possible targets for interventions. To turn these findings into useful control measures, we need to do more research and work together. J. Adv. Vet. Anim. Res., 12(1): 123–131, March 2025 http://doi.org/10.5455/javar.2025.l879